Impaired oxidation of debrisoquine in patients with perhexiline liver injury. Issue 10 (October 1984) - Morgan, M Y; Reshef, R; Shah, R R; Oates, N S; Smith, R L; Sherlock, S
Abstract : Perhexiline maleate is an antianginal agent which depends on hepatic oxidation for its elimination. Its use may be complicated by the development of peripheral neuropathy and liver damage. The majority of patients with perhexiline neuropathy have an impaired ability to effect metabolic drug oxidation which is genetically determined. Information has not been available on drug oxidation capacity in patients with perhexiline liver injury. Drug oxidation was measured using an oxidation phenotyping procedure in four patients with perhexiline liver injury and in 70 patients with chronic liver disease serving as a control group. All four patients with perhexiline liver damage showed a substantial metabolic defect; three of the four patients (75%) showed a genetically determined impairment of oxidation capacity. The incidence of severely impaired oxidation capacity in the perhexiline group was significantly greater than in the patients with chronic liver disease (6/70; 8.6%) and in the healthy population (9%) (F = 0.0048). A clear association exists between perhexiline liver injury and diminished drug metabolic activity, suggesting that the propensity to develop perhexiline liver injury is, at least in part, genetically determined.